تجارة التبغ في ولاية طرابلس الغرب خلال العهد العثماني الثاني 1835-1911م. (Journal of Humanitarian and Applied Sciences, 2023)
Abstract:Tobacco Cultivation and Trade Entered The State Of Tripoli in The west During The Nineteenth Century, Coinciding With The Return Of The Second Direct Ottoman Control Since 1835; This is due to The Ottomans, interest in Organizing The Country From The Administrative and political points of view , and then they set out to Develop Agriculture, Which became the First income for the State in General and Farms in particular. The Foreigner led by Reggae.